2018
DOI: 10.1055/s-0038-1641729
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Arm Assisted Total Knee Arthroplasty Demonstrated Greater Accuracy and Precision to Plan Compared with Manual Techniques

Abstract: This study determined if robotic-arm assisted total knee arthroplasty (RATKA) allows for more accurate and precise bone cuts and component position to plan compared with manual total knee arthroplasty (MTKA). Specifically, we assessed the following: (1) final bone cuts, (2) final component position, and (3) a potential learning curve for RATKA. On six cadaver specimens (12 knees), a MTKA and RATKA were performed on the left and right knees, respectively. Bone-cut and final-component positioning errors relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
185
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 44 publications
9
185
2
6
Order By: Relevance
“…A variety of femoral and tibial angular measures generally revealed significantly reduced bone cutting errors for the robotic-assisted group [14]. Unfortunately, no measures of planned vs achieved resection thicknesses were provided in that paper [14]. Study design and reporting differences make direct comparisons to the current work difficult, however, bone cut error variances in that report appear generally consistent with our current findings [14].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…A variety of femoral and tibial angular measures generally revealed significantly reduced bone cutting errors for the robotic-assisted group [14]. Unfortunately, no measures of planned vs achieved resection thicknesses were provided in that paper [14]. Study design and reporting differences make direct comparisons to the current work difficult, however, bone cut error variances in that report appear generally consistent with our current findings [14].…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, the number of knees used was not sufficient to reach any level of significance [13]. Another publication reported a cadaveric study comparing TKA implanted on cadavers with either a robotic-arm technique or a conventional instrument system [14]. In that comparative study, a single surgeon performed robotic-assisted or conventional instrument TKA on one leg each of 6 cadavers, for a total of 6 of each type [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce inadvertent soft tissue damage in a valgus case, it has been suggested that precise bone resections could be applied while maintaining the integrity of the soft tissue envelope. Robotic assisted (RA) technology has been shown to have three dimensional (3D) cut accuracy which could assist with addressing these complex cases [4]. The purpose of this work was to determine the number of soft tissue releases and component orientation of valgus cases performed with RA total knee arthroplasty (TKA).…”
mentioning
confidence: 99%